Insomnia and circadian sleep disorders in ovarian cancer: Evaluation and management of underestimated modifiable factors potentially contributing to morbidity. (29th October 2021) - Palagini, Laura; Miniati, Mario; Massa, Lucia; Folesani, Federica; Marazziti, Donatella; Grassi, Luigi; Riemann, Dieter
Abstract: Ovarian cancer is the leading cause of gynaecological cancer deaths and the seventh most commonly diagnosed cancer among women worldwide, so that, as it is related to substantial and increasing disease burden, the management of ovarian cancer survivors should be a priority. Such issues involve prevention and management of emotional distress, anxiety/depressive symptoms, and maintenance of quality of life from initial diagnosis to post‐treatment. Within this framework, sleep disturbances, in particular insomnia, are emerging as modifiable determinants of mental health, also contributing to substantial morbidity among cancer, including ovarian cancer. To this aim we conducted a systematic review according to PRISMA guidelines on prevalence and management of insomnia and circadian sleep disorders in ovarian cancer, while selecting 22 papers. Insomnia was evaluated in ovarian cancer and, while circadian sleep disturbances were poorly assessed in ovarian cancer, insomnia increased from 14% to 60% of patients. Insomnia was associated with cancer‐related comorbid conditions such as emotional distress, anxiety/depressive symptoms and low quality of life. Despite this evidence, no studies have been conducted about insomnia treatment in ovarian cancer. The burden of insomnia and circadian sleep disorders in patients with ovarian cancer still needs to be addressed, and requires a call to action for the evaluation and management of these potential modifiable factors that might contribute to ovarian cancer morbidity.